ANALISIS KINERJA LALU LINTAS JL. RAYA MR. MOCH. ICHSAN, KOTA SEMARANG (DEPAN PINTU KELUAR MASUK RS. PERMATA MEDIKA): Indonesia - syifafauziah ara putri; Reza Juliansa Prastica; Mudjiastuti Handajani; Yesina Intan Pratiwi (J-ENSITEC, 2022)
Semarang is one of the metropolitan. Traffic on Jl. Raya Mr Moch. Ichsan in front of the Permata Medika hospital, which is fairly crowded, is due to the influence of the hospital's activities. Many activities are seen at the entrance and exit of the hospital, including crossing. The purpose of this study was to analyze traffic performance, determine the factors that hinder traffic flow, determine the volume, travel time, and vehicle delay time due to u-turns at the median opening in front of the hospital entrance. Medical Gems. Traffic volume data collection was carried out for 3 days, namely weekdays, short days. and holidays using the 2014 PKJI method (referring to the reference to the 1997 MKJI basic rules). The results of the observations obtained are that the total current is 6201 cur/hour with the side resistance weight being at a moderate level. By following the 2014 PKJI guidelines, we get the adjustment values ​​for Free Flow Speed ​​(VB) = 61 km/hour and Capacity (C) = 7128 skr/hour. With a value of DJ = 0.869 cur/hour, it is at LOS level E which according to PKJI 2014 (referring to the reference to the 1997 MKJI basic rules) the level of road service is above the average for the maximum service level, namely levels A to D with a degree of saturation value of 0.00 - 0.84. Strict action from the relevant officers is needed by controlling existing traffic signs such as parking is prohibited in order to maximize the function of the existing road capacity.